The Performance of Marketing and Distribution on Supply Chain of Rice in Merauke Regency, Papua, Indonesia - Ineke Nursih Widyantari (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
AbstractMerauke is projected to be the rice barn in Eastern part of Indonesia. Many programmes are implemented to improve rice production. This study was conducted to figure out the number of distribution channels for rice marketing, to find out the efficient rice marketing actor, to recognise the smooth flow of product, money, and information on distribution of rice supply chain. The study was carried out in Merauke, i.e., districts of Semangga and Tanah Miring. Rice traders were sampled using the snowball technique, the initial point of farmers with 239 respondents. The results showed that there were four distribution channels of rice in Merauke. The most efficient rice marketing actor was the rice mill selling its product to Bulog partners. The pattern of the distribution of rice supply chain describing the flow of product, money and information was basically smooth, however, there was an unsmooth part in details. Keywords:Distribution, Marketing, Rice, Supply Chain